Collective storytelling as a river restoration tool: The role of catchment communities in inspiring environmental change - Doehring, Katharina; Cole, Cathy; Young, Roger G.; Longnecker, Nancy (Frontiers in Communication, 2023)
In Aotearoa New Zealand, catchment communities have been actively working to restore the health of their rivers, in some cases for many decades. Their knowledge offers a valuable resource that could motivate and empower other groups to do the same, making river restoration more effective at large scales. We spoke to five catchment groups across Aotearoa New Zealand to conceptualize and define how knowledge sharing through storytelling could be used as a tool to inspire freshwater restoration action amongst their own community and elsewhere. Each group created a ‘Catchment Journey’, a graphical artwork that told a story of their land and people, and their restoration activities. Whilst each of these ‘Journeys’ was unique, the following common elements were important for knowledge sharing: 1) the role of respected storytellers (e.g., community champions) in influencing restoration in their community; 2) recognition of responsibility to act (e.g., concern for future generations, land stewardship, prosperity and community cohesion); and 3) authenticity (e.g., true and honest stories, including weaknesses, threats and hardship). Participants recommended including each of these key elements in collective catchment storytelling to encourage large scale freshwater restoration.